Yemen in the 1990s : From Unification to Economic Reform - Choueiri, Nada.; Enders, Klaus-Stefan.; Sobolev, Yuri.; Walliser, Jan. (Washington, D.C. : International Monetary Fund, 2002)
The 1990s saw the unification of the two Yemens into one nation and a burgeoning of the country's oil sector. This paper examines the structural changes in the Yemeni economy brought about by these and other developments and identifies the reforms needed to move the country toward rapid and sustainable growth, effectively manage its oil wealth, and reduce the widespread poverty. The paper addresses the issue of poverty reduction by providing background and drawing lessons from Yemen's adjustment experience to date.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet